A balance of progressive cycle in Latin America - Svampa, Maristella (2018)
Taking into account the several epistemologies located at the South, the approach to the Brazilian crisis, the approach to the delegitimization or the decreasing political acceptance of the Latin American welfare-oriented government have been analyzed through three critical areas: the eco-territorial, the socioeconomic and the institutional policy. Those critical areas are useful as well to approach an understanding of the region as a whole, after studied the fifteen years of the Latin American welfareoriented government hegemony.